1987
DOI: 10.1007/bf02310102
|View full text |Cite
|
Sign up to set email alerts
|

An unconstrained dual program for computing convexC 1-spline approximants

Abstract: --ZusammenfassungAn Unconstrained Dual Program for Computing Convex C1-Spline Approximants. In the present paper the problem of approximating given data sets by convex cubic CX-splines is considered. To this programming problem a dual program is constructed which is unconstrained. Therefore an efficient computational treatment is possible. AMS (MOS)SubjectClassifications: 65D 10, 41A15, 90C20. Key words: Specia~y structured optimization problem, Fenchel dualization, return-formula.. Eine dnale Optimierongsaufg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

1990
1990
2003
2003

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 16 publications
2
13
0
Order By: Relevance
“…The functional (4.3) is widely in use for fitting given data (xo, Wo), (xl, wl) ..... (x,, w,); see [13], [4], [9] and several further papers. Now, tc is seen more dearly to be a parameter by means of which the compromise between curvature minimization and interpolation is controlled.…”
Section: Minimization Of a Regularized Mean Curvature: Discretizationmentioning
confidence: 99%
“…The functional (4.3) is widely in use for fitting given data (xo, Wo), (xl, wl) ..... (x,, w,); see [13], [4], [9] and several further papers. Now, tc is seen more dearly to be a parameter by means of which the compromise between curvature minimization and interpolation is controlled.…”
Section: Minimization Of a Regularized Mean Curvature: Discretizationmentioning
confidence: 99%
“…Then we show that the finite termination of the Newton method follows when the iterate p k is sufficiently close to a solution p * and it lies in the same piece U i as p * does. The finite termination property explains the numerically observed behavior of the Newton method that it terminates after a small number of steps when starting from a sufficiently good point [26,2,23,25].…”
Section: Finite Terminationmentioning
confidence: 99%
“…Based on those theoretical results, it is suggested that the (ordinary) Newton method is applied to (10) or equivalently to (11). Numerical experiments [2,[23][24][25] show that the Newton method terminates in a small number of steps (averaging 3−5 steps) if a sufficiently good starting point is used, which is often provided by the steepest descent method. The finite termination is even observed when starting from rough points.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations